Integration of Multi-Platform IoT System for Earthquake Detection via Telegram and WhatsApp - Satria Fitrah Nugraha; Mahesa Sangga Bhuwana; Dwi Taufik Hidayat (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
Earthquakes are natural disasters that can cause significant damage to infrastructure and endanger human lives. Therefore, early detection and rapid information dissemination are essential aspects of risk mitigation. Previous studies have developed earthquake detection systems based on the Internet of Things (IoT), but most were limited to a single communication platform, resulting in restricted information coverage and less optimal notification speed. This study aims to design and develop an IoT-based earthquake detection system integrated with multi-platform communication to provide real-time alerts via Telegram and WhatsApp applications. The system employs the MPU6050 sensor to detect ground vibrations, which are then converted into Richter Scale (SR) values as indicators of earthquake magnitude. If the SR value exceeds a certain threshold, the system automatically sends notifications to users through Telegram and WhatsApp, while simultaneously activating a buzzer and displaying information on the LCD. The test results indicate that the system can detect vibrations with SR values ranging from 0.67 to 5.10. The average notification delivery time was recorded at 1.4 seconds for Telegram and 2.6 seconds for WhatsApp. The contribution of this study is the integration of IoT with two popular communication platforms simultaneously, thereby expanding coverage, accelerating information delivery, and enhancing the effectiveness of earthquake disaster mitigation.